Training Needs Assessment of Agro-input Dealers in Banda District of Uttar Pradesh - Singh, Narendra; Gupta, B.K.; Gautam, U.S. (Indian Journal of Extension Education, 2021)
In Indian social structure agro-input dealers plays an important role in agricultural production and marketing system. They forms a strong link and contribute towards strengthening the Agricultural Extension System by providing valuable service to the farming community in a mode of technology dissemination. It is essential that they are equipped with latest agriculture knowledge through refresher training courses. The present investigation was conducted during 2017-18 at Banda University of Agriculture and Technology in Banda district of Uttar Pradesh at the time of starting Diploma in Agriculture Extension Services for Input Dealers (DAESI) programme to ascertain training needs of agro-input dealers. Data was collected through personal interview and written feedback of 40 retailers using structured interview schedule. 95 per cent respondents were male and found to be highly educated with >52 per cent of them having senior secondary and higher degrees. 80% input dealers belong to young and middle age group and 77.5 percent were dependent on bank credit for the business. Respondents ranked 1st priority of training needs in package of practices of major crops, rabi weed management, government laws and regulation of fertilizers, insect-pest management of pigeon pea & gram, cattle farming, filing of GST & E-billing, respectively. Training in computer and its application in business was another preferred area. Lack of need based training, complications in GST filling and low profit in the business were some of the constraints identified by the input dealers of Banda district.
Keywords: Training need assessment; Agro-input dealers; Subject matter; Constraints